IMPROVING STUDENTS’ ABILITY IN READING COMPREHENSION THROUGH COOPERATIVE LEARNING OF TAI (TEAM ASSISTED INDIVIDUALIZATION) - Ermawati Zulikhatin Nuroh; Vidya Mandarani (UAD TEFL International Conference)
One of the learning models based on student activities (Students Centered Learning) is by using cooperative learning of TAI (Team Assisted Individualization) on the learning process in the classroom. This research is intended to know the improving reading comprehension through cooperative learning model of TAI (Team Assisted Individualization). This research used quantitative research using experimental design type one group pretest-posttest design with the sample student of semester 1 Diploma III Midwifery Program of Universitas Muhammadiyah Sidoarjo. The result of the research shows that there is a significant improvement toward the first semester students of Diploma III Midwifery Program by using cooperative learning model of TAI type (Team Assisted Individualization). This can be seen from some calculations such as pre-test average X = 44,32 and average post- Test Y = 66.56 from the average pre-test and post-test posttest is higher than the pre-test. (Compare) with 5% significant level of degree of freedom (df) = (n-1) = 28, whether t value> t table. There is improvement in reading comprehension through cooperative learning model type TAI (Team Assisted Individualization) toward the first semester students of Diploma III Midwifery Program of 0.07> 0.14. This research is expected to contribute to the learning model of reading comprehension to improve students' ability.